Thoracopagus conjoined twins: a case report - Satpathy, Rabi Narayan; Das, Om Avishek; Swain, Sujata; Nanda, Amrita; Sahoo, Balaram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
25 yr. old, G2P1 presented with premature labour pains at 33wks 3d of gestation and was referred to our tertiary centre as a suspected case of conjoined twin pregnancy based on a sonography report which revealed fetus with two heads Decision in favour of LSCS was taken after counselling the patient and her attendants regarding the anomaly of the fetus and incompatibility of life and dangers of spontaneous vaginal delivery. LSCS was done with delivery of first twin by cephalic and second twin by breech extraction, both were preterm male babies joined anteriorly starting from thorax to umbilicus (Thoracopagus) with four arms and four legs, baby could not be revived and was declared clinically dead in few minutes by neonatologist,. Photographs were taken and we tried to obtain consent for autopsy but attendants were reluctant. A review of the literature suggests that early diagnosis by a combination of ultrasound and MRI is essential to management, providing prognosis for viability and success of surgical separation and the opportunity for early counselling of parents and termination if indicated.